An efficient cryptographic scheme for text message protection - N K, Manikandan; D, Manivannan; kumar K, Antony (International Journal of Engineering and Technology, 2018)
Interchange of information is increasing very rapidly. Transferring any information on internet arises with the biggest issue that is security. Cryptography plays an important role in achieving security. For any type of business our primary focus is mainly on the security of information for that we require a robust and unbreakable process that provides great safety. This project is concerned with the development of a secure messaging system based on cryptographic algorithm that is which is more faster, better immune to attacks, more complex, easy to encrypt. This is well featured and provides encryption/decryption that can protect message from unauthorized access. we proposed an algorithm, which uses triple keys for encryption and decryption of text to secure the information. This application is well featured and provides security that can protect message from unauthorized access. To send a message, a sender types and encrypts a text message using Three Keys algorithm with a key selected from keylist .The encrypted message is stored in database and receiver’s inbox serial number of key .The receiver, after logging into account ,selects key value and then decrypts with key to see the original message